Amerikai offshore világgazdaság - Czakó, Zsuzsaanna (Debreceni Jogi Műhely, 2009)
The problem I am looking into is a world-wide phenomenon called money-laundering. This topic is important because the money it involves is such a big amount that it endangers the operation of both national and world economics. It is called “second economics” and serves as the third largest business branch in the world after currency exchange and oil. Money laundering has not been put into the centre because of that fact that it has been discovered in the past ten years, but because it became so widespread and hazardous that fighting against it is now highly required. It is evident that money laundering is a world-wide problem. It is also highly probable that the popularity of this crime will not decrease in the next years. One can ask why it is a world- wide problem. As music does not know any limits, neither does money laundering. That is, the base crime and the laundering can be committed anywhere in the world. My study is intended to take a closer look on the offshore bank system, to examine the American laws involved, to present the views and political ideas of those laws and scrutinize the role of offshore accounts in the development of the global financial crisis. I chose to present the characteristics of the offshore bank system because I found it important to analyze money laundering extensively through the bank system in a state where the term “money laundering” was first printed and published in 1973. It first appeared in an article about the Watergate-scandal. The first court to use the term in criminal law was an American court in 1967 and it was also in this state that money laundering became an independent crime, in 1986. The notion of organized crime also appeared here in the 1920’s. Regulations against money laundering arrived to Europe from the United States of America, which means that it illustrates the Americanization of European criminal law. Money laundering is a serious problem – a business and financial apocalypse -  that now deserves a Draconian arrangement. Should this arrangement not happen, the prospective for the future is frightening. The United Stated should act as a model in the spring-cleaning of the global financial system and the financial sector should take the role of an initiator. We would like other societies to be the models and to start fighting against things they have initiated. One thing is for sure, the American legislative is desperate because they believe that there is a lot at stake: the American capitalism.